2018
DOI: 10.1108/k-12-2017-0497
|View full text |Cite
|
Sign up to set email alerts
|

A novel fuzzy risk matrix based risk assessment approach

Abstract: Purpose Traditional risk assessment (RA) methodologies cannot model vagueness in risk and cannot prioritize corrective-preventive measures (CPMs) by considering effectiveness of those on risk types (RTs). These cannot combine and reflect accurately different subjective opinions and cannot be used in a linguistic manner. Risk factors (RFs) are assumed to have the same importance and interrelations between RFs are not considered. This study aims to overcome these disadvantages by combining fuzzy logic with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 67 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…The theory of fuzzy numbers has been widely applied in risk analysis [10], approximate reasoning [11], and risk pattern recognition [12]. For risk analysis, the existing methods can be divided into the fuzzy ranking-based [13], fuzzy inference-based [14,15], fuzzy matrix-based [16,17], and fuzzy number similarity-based [9] risk assessment models. Zhang et al [13] figure out the risky area based on a water security evaluation framework by comparing the risk of related areas.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of fuzzy numbers has been widely applied in risk analysis [10], approximate reasoning [11], and risk pattern recognition [12]. For risk analysis, the existing methods can be divided into the fuzzy ranking-based [13], fuzzy inference-based [14,15], fuzzy matrix-based [16,17], and fuzzy number similarity-based [9] risk assessment models. Zhang et al [13] figure out the risky area based on a water security evaluation framework by comparing the risk of related areas.…”
Section: Related Workmentioning
confidence: 99%
“…However, fuzzy inferencebased methods are usually used in industry and are not suitable for trial applications. Can et al [16] present a three-stage fuzzy risk matrix-based risk assessment and dynamically combine multicriteria decision-making with fuzzy logic. Though fuzzy matrix-based methods can reduce risk ties [19] efficiently, they still provide a qualitative assessment that is not precise enough.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, Marhavilas et al (2011) classified the classic risk analysis and evaluation methods into three classes: qualitative, quantitative, and hybrid approaches. According to literature, the classical methods do not meet the requirements and must be enhanced to analyze the risks of work environments, which have become more complex (Can & Toktas, 2018, Goerlandt et al, 2017, Mohsen & Feresteh, 2017& Mutlu & Altuntas, 2019b. Some researchers have suggested that classical risk analysis and evaluation methods should be developed by hybridizing the methods with fuzzy logic, multi-criteria decision-making methods (Dabbagh & Yousefi, 2019, Tepe & Kaya, 2019, Gul, 2019, Akyildiz & Mentes, 2017& Gürcanlı & Müngen, 2009.…”
Section: Hazard and Risk Assessment And Research Hypothesismentioning
confidence: 99%
“…Range of likelihood and consequences are grouped together to form a ranking for the risks (Bucelli et al, 2018). Likelihood is described as the probability of potential consequences to occur throughout the life of the individuals; whilst, consequence is refers to the impact of the event and the severity of the impact to an individual if it happen (Can & Toktas, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Identified risks are often assessed in terms of consequences and likelihood (Pfitzer & Clemens, 2006). Risk is assesses by assigning values to each of the risks through the defined criteria (Can & Toktas, 2018). Subsequently, the priorities of risk are determined by comparing the level of risk against predetermined target risk levels and acceptance thresholds (Curtis & Carey, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%